Anti-social bandits culture resistance and the Tsotsi subculture on the Witwatersrand during the 1940s and 1950s - Glaser, Clive (My University, 1990)
Witwatersrand during the 1940s and 1950s never involved themselves in "politics". Because they were almost by definition unemployed they were also marginal to the struggle between capital and labour. A study of the tsotsi subculture is therefore in danger of becoming politically irrelevant, a colourful sociological study detached from broader social power struggles. This paper attempts to offset this danger from the outset by broadening the definition of "political" to embrace culture and ideology. I will place the tsotsi subculture within the context of the struggle for cultural hegemony in South Africa. Not only did the tsotsi subculture occupy a significant niche within the cultural fabric of urban South Africa, but, I will argue, it represented a powerful counter-force to the cultural hegemonic status quo. (1)
African Studies Seminar series. Paper presented September, 1990
Keywords: Urban youth. South Africa. Witwatersrand. Social conditions; Gangs. South Africa. Witwatersrand; Gangs. Political activity. South Africa. Witwatersrand